Association among hsCRP Levels, Bone Mineral Density, and Periodontal Parameters in Postmenopausal Women - Baldodia, Aastha; Sharma, Rajinder kumar; Tewari, Shikha; Arora, Aman (UI Scholars Hub, 2021)
Association of Osteoporosis and periodontitis is well documented. Osteopenia being the initial state of bone loss prior to osteoporosis; finding its correlation with clinical attachment loss holds significance in the process of establishing early reduction in BMD as a risk factor for periodontitis. Objectives: The present cross sectional study aimed to explore the association of osteopenia with serum high sensitivity C-reactive protein (hsCRP) levels, and periodontal parameters in narrow age range postmenopausal (PM) women. Methods: 112 participants in this single centred cross sectional study were bifurcated into test group: osteopenic PM women [n=62], and control group: normal bone mineral density [BMD] PM women [n=50]. BMD, serum levels of hsCRP, and periodontal parameters were recorded. Results: Clinical attachment loss [CAL] and hsCRP were found to be signiﬁcantly higher in the osteopenic PM group. Conclusion: An association of osteopenia with increased CAL in PM women was found, implicating postmenopausal osteopenia associated with increased risk of periodontitis. The present study hints towards the comprehensive management of Periodontitis and osteopenia in postmenopausal women by maintaining a good coordination between the physicians and dentists.